Impact of Interest Congruence on Study Outcomes - Ertl, Bernhard; Hartmann, Florian G.; Wunderlich, Anja (Frontiers in Psychology, 2022)
Grounding on Holland’s RIASEC model of vocational interests and the respective assumptions on person-environment fit (congruence), this paper focuses on how congruence is related to study outcomes, especially students’ persistence, performance, and satisfaction. The paper distinguishes the measure of congruence with respect to social congruence (interest fit with the study mates) and aspirational congruence (interest fit with the occupation aspired) and also distinguishes the effects of congruence for gender and six different study areas including STEM, medicine, economics, education, and languages. The paper analyses 10,226 freshmen of the German National Educational Panel Study (NEPS) and follows them longitudinally with respect to their study outcomes. The results show that students’ persistence was more related to social than to aspirational congruence, especially for male students. Furthermore, social congruence was particularly important for students in STEM areas. Regarding performance, however, aspirational congruence was more important. Here, we notably found correlations for STEM subjects with a balanced proportion of female students. Regarding satisfaction, mainly marginal correlations could be found. The results indicate conceptual differences between social and aspirational congruence as well as specific effects for gender and study area. While research might take this into account by developing their models specific for different study areas, career counselling may reflect on the different significance of the interest-based person-environment fit for different study areas. Initiatives for raising young people’s participation in STEM should therefore specifically focus on students that have high chances to develop interest profiles that are congruent to STEM rather than students who have profiles that already indicate a low congruence.